Alternative indicators of Universidad Central “Marta Abreu” of Las Villas scientific activity in the Web 2.0 - Alejandor Céspedes Villegas; María Josefa Peralta González; Luis Ernesto Paz Enrique (Cuadernos de Documentación Multimedia, 2017)
At present day to the use of Web 2.0 for academic purposes, have been generated alternative indicators to measure scientific output in these new platforms. At the Universidad Central "Marta Abreu" de Las Villas is identified a considerable presence of professionals that make intensive use of social and academic networks in order to share their scientific production and promote their visibility. In the center of higher education is unknown the visibility and scientific impact by the users in social networks and Web 2.0 platforms. Is presented as objective of the study to describe the scientific activity of the Universidad Central “Marta Abreu” de Las Villas in Web 2.0, using alternative indicators. To obtain results are used methods in the theoretical and empirical levels, highlighting the bibliometric method. Are identified the users who have more publications and calculate him several indicators within academic networks Research Gate, Google Scholar and comparisons are made with the results obtained on both platforms.